Fiscal Rules and Effective Fiscal Policy - Działo, Joanna (Comparative Economic Research. Central and Eastern Europe, 2012)
This article examines and assesses the influence of political factors on the effectiveness of pursuing fiscal policy. These factors usually cause and maintain a high budget deficit and public debt. Moreover, the problems of influence of fiscal rules on increased effectiveness of the pursued fiscal policy have been discussed. The fiscal rules are to assure macroeconomic stability in economy and improve credibility of the pursued fiscal policy by reducing the deficit, government spending, and public debt. Examples of applicable fiscal rules in the EU and Poland are presented and an attempt is made to evaluate the effectiveness of these rules in the process of consolidation of public finances.